2019
DOI: 10.12659/msm.911444
|View full text |Cite
|
Sign up to set email alerts
|

Intraperitoneal Injection of Acetate Protects Mice Against Lipopolysaccharide (LPS)‑Induced Acute Lung Injury Through Its Anti-Inflammatory and Anti-Oxidative Ability

Abstract: Background As a member of short-chain fatty acids, acetate exhibits anti-inflammatory capacity. The present study aimed to investigate the effect of acetate on lipopolysaccharide (LPS)-induced acute lung injury (ALI) and explored its underlying mechanism. Material/Methods Acetate (250 mM, 400 μL) was given intraperitoneally 30 minutes after LPS (5 mg/kg) intratracheal injection. Lung tissues and bronchoalveolar lavage fluid (BALF) were collected 6 hours after the challe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…In the present work, in both blood plasma and brain tissues of mice, an increase in the concentration of acetate was detected, even though, under normal circumstances, the concentration of acetate in circulation is low (e.g., 199.9 μmol/L in group C) [35]. Elsewhere, acetate has been found to be produced during endogenous bacterial fermentation in the gut as a protective response [36].…”
Section: Discussionsupporting
confidence: 41%
“…In the present work, in both blood plasma and brain tissues of mice, an increase in the concentration of acetate was detected, even though, under normal circumstances, the concentration of acetate in circulation is low (e.g., 199.9 μmol/L in group C) [35]. Elsewhere, acetate has been found to be produced during endogenous bacterial fermentation in the gut as a protective response [36].…”
Section: Discussionsupporting
confidence: 41%
“…A few studies have shown that acetate has anti-inflammatory effects [ 43 - 46 ], while direct evidence showing its role in pain modulation is lacking. The levels of acetic and propionate acids decrease remarkably in patients with inflammatory bowel disease compared to healthy individuals [ 47 ].…”
Section: Association Between Scfas and Chronic Painmentioning
confidence: 99%
“…In a rat model of LPS-induced neuroinflammation, acetate supplementation exerts potent anti-inflammatory and neuroprotective effects by reducing pro-inflammatory cytokine expression and attenuating neuroglial activation [ 44 , 45 ]. Anti-inflammatory and anti-oxidative effects of acetate have been reported in an LPS-induced mouse model [ 46 ].…”
Section: Association Between Scfas and Chronic Painmentioning
confidence: 99%
“…Butyric acid reduces systemic inflammation by inhibiting the STAT1/AP1 signaling pathways in peritoneal macrophages, as well as the secretion of NLRP3 inflammasomes and pro-inflammatory factors [54]. Similarly, acetate alleviates the inflammatory response of the organism by exerting its antibacterial, anti-inflammatory, and antioxidant properties [109,110]. In addition, valproic attenuates AP by reducing myeloperoxidase activity and the local tissue destruction of other organs [111].…”
Section: Supplementation Of Metabolitesmentioning
confidence: 99%